First Report of Pepper chat fruit viroid in Traded Tomato Seed, an Interception by Australian Biosecurity - Chambers, G A (Plant disease, 2013)
Pepper chat fruit viroid (PCFVd), a species of Pospiviroid, was first discovered in a capsicum crop in the Netherlands in 2006 (4) and was then reported only in Thailand (2) and Canada. The mechanism of international spread was not known, but movement with traded seed was suspected. PCFVd is transmissible through capsicum seed (4) and very probably through tomato seed, like other pospiviroids. The viroid causes disease in capsicum and tomato and experiments by others indicate a capacity to cause disease in potato. It poses a biosecurity threat to crops internationally. PCFVd was intercepted by the Australian Government Department of Agriculture, Fisheries, and Forestry (DAFF) in five shipments of tomato seed (Solanum lycopersicum) exported from Israel and Thailand in September and October 2012. Batches of up to 20,000 seeds were sampled from each seed lot in a shipment and total nucleic acids were extracted from sub-samples, each of about 400 seeds, following a method similar to Hoshino et al. (1). PCFVd was initially detected when reverse transcription PCR using the generic pospiviroid primers Pospi1-FW and Pospi1-RE (3) produced amplicons of 189 bp, which were then sequenced. The PCFVd specific primers AP FW1 and AP RE2 (4) were used to amplify the remainder of the viroid genome, which was directly sequenced. Overlapping sequences were aligned to produce complete sequences of 349 bases, one from seed from Thailand and two from seed from Israel (GenBank: KC762952, KC762953, KC762954). Searches of the GenBank nucleotide non-redundant database indicated close matches with sequences from PCFVd isolates from tomato in Thailand (2); alignments generated by BLAST showed the sequences differed from those from Thailand at only 2 to 18 nucleotide positions, equating to 95 to 99% identity. PCFVd sequences from seed from Thailand were almost identical (>99%) to the sequences from seed from Israel. Many sub-samples were negative, indicating that the number of contaminated seeds was very small in some shipments. The positive sub-samples as a proportion of the total number of sub-samples tested from the five shipments was 1/1, 1/5, 1/1, 12/50, and 7/50. Tomato and capsicum seed are produced in many countries and often traded through second countries. The infected tomato seed shipments intercepted by DAFF were destroyed or re-exported following Australian regulations. Other countries were informed through the International Plant Protection Convention. This pest viroid has not been intercepted by Australian authorities before and has not been detected in recent Australian survey work (data not shown). References: (1) S. Hoshino et al. Res. Bull. Plant Prot. Japan 42:75, 2006. (2) K. Reanwarakorn et al. New Dis. Rep. 24:6, 2011 (3) J. Th. J. Verhoeven et al. EJPP 110:823, 2004. (4) J. Th. J. Verhoeven et al. Virus Res. 144:209, 2009